Measurement of the branching fraction of D + → τ + ν τ - The BESIII collaboration; M. Ablikim; M. N. Achasov; P. Adlarson; O. Afedulidis; X. C. Ai; R. Aliberti; A. Amoroso; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Journal of High Energy Physics, 2025)
Abstract By analyzing e + e − collision data with an integrated luminosity of 7.9 fb −1 collected with the BESIII detector at the center-of-mass energy of 3.773 GeV, the branching fraction of D + → τ + ν τ is determined as B $$ \mathcal{B} $$ = (9.9 ± 1.1stat ± 0.5syst) × 10 −4. Using the most precise result B $$ \mathcal{B} $$ (D + → μ + ν μ ) = (3.981 ± 0.079stat ± 0.040syst) × 10 −4 [1], we determine R τ/μ = Γ(D + → τ + ν τ )/Γ(D + → μ + ν μ ) = 2.49 ± 0.31, achieving a factor of two improvement in precision compared to the previous BESIII result. This measurement is in agreement with the standard model prediction of lepton flavor universality within one standard deviation.